2020
DOI: 10.31004/jrpp.v3i2.1230
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Video Animasi Terhadap Pengetahuan Konsep Pola Anak Usia 5-6 Tahun

Abstract: Penelitian ini dilakukan untuk menghasilkan produk berupa Video Animasi Terhadap Pengetahuan Konsep Pola Anak Usia 5-6 Tahun. Jenis penelitian ini adalah penelitian dan pengembangan (Research and Development).Hasil dari penelitian dan pengembangan ini mengacu pada langkah yang dikemukakan oleh Sugiyono (2016); 1) potensi dan masalah. 2) pengumpulan data dan informasi. 3) desain produk. 4) validasi produk; (a) uji ahli materi; (b) uji ahli media. 5) revisi produk; (a) teknik pengumpulan data; (b) observasi; (c)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
27

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 0 publications
0
9
0
27
Order By: Relevance
“…Video design is made relevant to the learning process, where the content of the video begins with apperception activities, providing material, providing evaluation questions, and closing. As stated by Riyana (2007), video media development goes through several plans such as preparing the devices that will be used, and making a video framework that includes determining the introduction, opening show, introduction, video content, and closing.…”
Section: Discussionmentioning
confidence: 99%
“…Video design is made relevant to the learning process, where the content of the video begins with apperception activities, providing material, providing evaluation questions, and closing. As stated by Riyana (2007), video media development goes through several plans such as preparing the devices that will be used, and making a video framework that includes determining the introduction, opening show, introduction, video content, and closing.…”
Section: Discussionmentioning
confidence: 99%
“…Very less valid Modified from Riyana, et al (2020:258), Apriansyab, et al (2019 Based on table 2, it can be concluded that the learning video is said to be valid if the achievement target reaches a valid value of >65%. The amount of the assessment results of students and teachers will be calculated as a percentage so that the level of practicality of the animated video can be known using the following formula:…”
Section: Data Analysis Techniques Validity Questionnaire Data Analysismentioning
confidence: 99%
“…The next stage calculates the average number of percentages of all respondents using the formula: Riyana, et al (2020:258), Apriansyab, et al (2019 Based on table 4, it can be concluded that animated videos are said to be practical if the achievement target reaches a practical value of >75%.…”
Section: Practicality Questionnaire Analysismentioning
confidence: 99%
“…Tujuan dari media video adalah untuk menyajikan informasi dalam bentuk yang menyenangkan, menarik mudah dimengerti dan jelas. Informasi akan mudah dimengerti karena sebanyak mungkin indera, terutama telinga dan mata, digunakan untuk menyerap informasi itu (Riyana, 2017).…”
Section: Media Videounclassified